Karakteristik Habitat Alami Ikan Lembat (Clarias leiacanthus) Di Desa Bandar Tinggi Ditinjau Dari Beberapa Parameter Faktor Kimia Perairan - Helentina Mariance Manullang; Khairul (Universitas Hasanuddin, 2021)
Slender walking catfish (Clarias leiacanthus) is a type of wild catfish that has been increasingly difficult to find in nature. This catfish is most wanted as fish consumption and the price is quite high, because of its distinctive and savory meat flavor. The natural habitat of slender walking catfish in general is clear and unpolluted waters. One of the habitats of slender walking catfish found in the Swimming Niagara Sirao-rao, Desa Bandar Tinggi, Labuhanbatu Regency. The study of the natural habitat characteristics of C. leiacanthus in this region has never been done. The purpose of this research is to know the chemical factors of water that become natural habitat of C leiacanthus. Analysis of water samples related to pH, DO, BOD, and COD was conducted in the Laboratorium Balai Riset dan Standardisasi Industri Medan, used method AAS. Results of the analysis showed pH (6,5), DO (6,9 mg/L), BOD (3,27mg/L), and COD (8,26 mg/L).